Federal Democratic Republic Nepal: Deepening Problems and Prospects - Chetri, Than Bahadur (Journal of Political Science, 2018)
Constructing federal democratic republic is a complex process. Both old and new democracies face different forms of challenges in building and maintaining, either internally or externally. Hence, this paper assesses the challenges in developing and maintaining democratic republic Nepal. With the help of secondary sources of information, it argues, building democracy in Nepal is undermined by foundational challenges and deepening challenges. Nepal, a closer analysis from the perspective of the constitution, geography and national wealth, rule of law, the nature of the party and their leaders, the prospect of a democratic republic is unclear. Journal of Political Science, Volume XVIII, 2018, Page: 114-142